Suppression of PTRF Alleviates Post-Infectious Irritable Bowel Syndrome via Downregulation of the TLR4 Pathway in Rats - Zhou, Hui-hui; Zhang, Ye-ming; Zhang, Sheng-peng; Xu, Qi-xiang; Tian, Ya-qing; Li, Ping; Cao, Di; Zheng, Yong-qiu (Frontiers in Pharmacology, 2021)
Background: Accumulating evidence suggests that the polymerase I and transcript release factor (PTRF), a key component of the caveolae structure on the plasma membrane, plays a pivotal role in suppressing the progression of colorectal cancers. However, the role of PTRF in the development of functional gastrointestinal (GI) disorders remains unclear. Post-infectious irritable bowel syndrome (PI-IBS) is a common functional GI disorder that occurs after an acute GI infection. Here, we focused on the role of PTRF in the occurrence of PI-IBS and investigated the underlying mechanisms. Methods: Lipopolysaccharide (LPS) (5 μg/ml) was used to induce inflammatory injury in human primary colonic epithelial cells (HCoEpiCs). Furthermore, a rat model of PI-IBS was used to study the role of PTRF. Intestinal sensitivity was assessed based on the fecal water content. A two-bottle sucrose intake test was used to evaluate behavioral changes. Furthermore, shRNA-mediated knockdown of PTRF was performed both in vitro and in vivo. We detected the expression of PTRF in colonic mucosal tissues through immunohistochemistry (IHC), western blotting (WB), and immunofluorescence (IF) analysis. Luciferase activity was quantified using a luciferase assay. Co-localization of PTRF and Toll-like receptor 4 (TLR4) was detected using IF analysis. The activation of the signaling pathways downstream of TLR4, including the iNOs, p38, extracellular signal-regulated kinase (ERK), and c-Jun N-terminal kinase (JNK) pathways, was detected via WB. The levels of NO, IL-1β, IL-6, and TNF-α were measured using enzyme-linked immunosorbent assays. Results: LPS significantly induced PTRF expression and signaling downstream of TLR4, including p38, ERK, and JNK pathways, in HCoEpiCs. Moreover, shRNA-mediated knockdown of PTRF in HCoEpiCs significantly decreased the phosphorylation of JNK, ERK, and p38 and iNOS expression. In PI-IBS rats, the lack of PTRF not only reduced fecal water content and suppressed depressive behavior but also increased the body weight. Furthermore, we found a strong co-localization pattern for PTRF and TLR4. Consistently, the lack of PTRF impaired TLR4 signaling, as shown by the decreased levels of p-JNK, p-ERK, and p-p38, which are upstream factors involved in iNOS expression. Conclusion: PTRF promoted PI-IBS and stimulated TLR4 signaling both in vitro and in vivo. The results of this study not only enlighten the pathogenesis of PI-IBS but also help us understand the biological activity of PTRF and provide an important basis for the clinical treatment of PI-IBS by targeting PTRF.